Parameter estimation of discrete-time sinusoidal signals: A nonlinear control approach. (November 2019) - Jiang, Teng; Xu, Dabo; Chen, Tianshi; Sheng, Andong
Abstract: This paper considers a parameter estimation problem for discrete-time sinusoidal signals in the presence of measurement noise. Different from most of existing methods, we shall solve the problem based on nonlinear control theory. Specifically, we introduce a constructive nonlinear estimator that enables us to prove an interesting input/output stability property from measurement noise to estimation error. To show efficacy of the proposed method, we also present several numerical examples using different types of signals and noises.